2019
DOI: 10.1016/j.chempr.2019.04.015
|View full text |Cite
|
Sign up to set email alerts
|

2D sp2 Carbon-Conjugated Covalent Organic Frameworks for Photocatalytic Hydrogen Production from Water

Abstract: This work demonstrates a platform for designing a photocatalyst to promote lightdriven production of hydrogen from water. The newly developed photocatalyst consists of all sp 2 carbon frameworks that are fully p conjugated to promote exciton migration and offer a narrow band gap to harvest visible and near-infrared light. Engineering the lattice periphery with electron-deficient units tunes the band structure and constitutes built-in interfaces to generate electrons. The resulting frameworks enable efficient, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
371
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 486 publications
(389 citation statements)
references
References 48 publications
15
371
0
3
Order By: Relevance
“…[150] Thef ully p-conjugated sp 2 c-COF ( Figure 34) [151] with electron-accepting units at the lattice periphery exhibits greatly enhanced evolution of H 2 from water compared to imine-linked analogues and amorphous porous polymers. [152] Va rious semiconducting COFs with different band structures have been tested for photoinduced water splitting; nevertheless,the studies are still in their infancy.T oovercome the limitations,i ti sn ecessary to combine both water reduction and oxidation sites in one skeleton, and this deserves further research efforts.Adirect comparison of the photoenergy conversion efficiency of different systems on the basis of the H 2 evolution rates is difficult. This is because the rate is dependent on the light source,w avelength, device set up,a nd experimental scale.I nt he literature,d irect comparisons are often attempted, but this may cause misleading and unfair judgments to be made.Asafe way is to use the quantum yield that is determined by the number of electrons used in the H 2 evolution divided by the number of photons absorbed by the system.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[150] Thef ully p-conjugated sp 2 c-COF ( Figure 34) [151] with electron-accepting units at the lattice periphery exhibits greatly enhanced evolution of H 2 from water compared to imine-linked analogues and amorphous porous polymers. [152] Va rious semiconducting COFs with different band structures have been tested for photoinduced water splitting; nevertheless,the studies are still in their infancy.T oovercome the limitations,i ti sn ecessary to combine both water reduction and oxidation sites in one skeleton, and this deserves further research efforts.Adirect comparison of the photoenergy conversion efficiency of different systems on the basis of the H 2 evolution rates is difficult. This is because the rate is dependent on the light source,w avelength, device set up,a nd experimental scale.I nt he literature,d irect comparisons are often attempted, but this may cause misleading and unfair judgments to be made.Asafe way is to use the quantum yield that is determined by the number of electrons used in the H 2 evolution divided by the number of photons absorbed by the system.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[147,149] [150] Die vollständig p-konjugierten sp 2 c-COFs (Abbildung 34) [151] mit Elektronenakzeptoreinheiten an der Gitterperipherie zeigen eine deutlich stärkere H 2 -Bildung aus Wasser als iminverknüpfte Analoga und amorphe porçse Polymere. [152] Verschiedene…”
Section: Halbleiterunclassified
“…For improving the photocatalytic performance, the crystallinity and hydrophilicity of the photocatalyst are reported to be the crucial factors. For example, imine‐linked COFs based on sulfone unit have shown excellent photocatalytic hydrogen evolution performance due to the good hydrophilicity and crystallinity, whereas the study in hydrophilic CTFs is rarely demonstrated.…”
Section: Introductionmentioning
confidence: 99%